Quantification of epigenetic and genetic 2nd hits in CDH1 during hereditary diffuse gastric cancer syndrome progression - Oliveira, C (2009)
BACKGROUND & AIMS: Hereditary diffuse gastric cancer (HDGC) families carry CDH1 heterozygous germline mutations; their tumors acquire complete CDH1 inactivation through "2nd-hit" mechanisms. Most frequently, this occurs via promoter hypermethylation (epigenetic modification), and less frequently via CDH1 mutations and loss of heterozygosity (LOH). We quantified the different 2nd hits in CDH1 occurring in neoplastic lesions from HDGC patients. METHODS: Samples were collected from 16 primary tumors and 12 metastases from 17 patients among 15 HDGC families; CDH1 mutations, LOH, and promoter hypermethylation were analyzed. E-cadherin protein expression and localization were determined by immunohistochemistry. RESULTS: Somatic CDH1 epigenetic and genetic alterations were detected in lesions from 80% of HDGC families and in 75% of all lesions analyzed (21/28). Of the 28 neoplastic lesions analyzed, promoter hypermethylation was found in 32.1%, LOH in 25%, both alterations in 17.9%, and no alterations in 25%. Half of the CDH1 2nd hits in primary tumors were epigenetic modifications, whereas a significantly greater percentage of 2nd hits in metastases were LOH (58.3%; P = .0274). Different neoplastic lesions from the same patient frequently displayed distinct 2nd-hit mechanisms. Different 2nd-hit mechanisms were also detected in the same tumor sample. CONCLUSION: The 2nd hit in CDH1 frequently occurs via epigenetic changes in HDGC primary tumors and LOH in metastases. Because of the concomitance and heterogeneity of these alterations in neoplastic lesions and the plasticity of hypermethylated promoters during tumor initiation and progression, drugs targeting only epigenetic alterations might not be effective, particularly in patients with metastatic HDGC.